Morrey's the elbow and its disorders - Morrey, Bernard F. 1943-; Sanchez-Sotelo, Joaquin; Morrey, Mark E. (Elsevier, 2018)
"Revised to include the most up-to-date surgical techniques and their outcomes, Morrey's The Elbow and Its Disorders, 5th Edition, is an essential reference for today's orthopaedic surgeons, appealing both to those in general practice and those with a subspecialty interest in elbow surgery. This edition by Drs. Bernard Morrey, Mark Morrey, and Joaquin Sanchez-Sotelo, provides a practical focus on technique - both in the text and on dozens of high-quality instructional videos produced at the Mayo Clinic. Authoritative guidance from leading experts enables you to provide optimal care to your patients - even those with the most challenging elbow problems"--Publisher's description
Revised edition of: The elbow and its disorders / [edited by] Bernard F. Morrey, Joaquin Sanchez-Sotelo. 4th ed. ©2009
Includes bibliographical references
Keywords: Elbow / Diseases; Elbow / Wounds and injuries; Elbow Joint; Elbow Joint / injuries; Joint Diseases; Elbow -- Diseases; Elbow -- Wounds and injuries; Ellbogengelenkkrankheit